Pengaruh Model Pembelajaran RANDAI Terhadap Keterampilan Pemecahan Masalah Siswa SMA Pada Materi Fungi - Firdaus, Andiani; Arsih, Fitri; Alberida, Heffi; Fajrina, Suci (BEST Journal (Biology Education, Sains and Technology), 2023)
One of the 21st century skills needed to face the 4.0 revolution era is problem solving skills. However, these skills have not been fully mastered by students so that they can be improved through the application of the RANDAI learning model. This study aims to determine the effect of the RANDAI learning model on improving students' problem solving skills on fungi material at SMA Pertiwi 1 Padang. This research is an experimental research with Pretest-Posttest Control Group Design. The study population was the entire X IPA class of SMA Pertiwi 1 Padang. The research sample was X IPA 1 class students as the control class and X IPA 2 for the experimental class. The sampling technique was purposive sampling technique. The research instrument used 6 essay questions. The data analysis used paired sample t-test. Based on the research results, the experimental class students' problem solving ability scores were higher than the control class. The results of the paired sample t-test obtained a significant value of 0.000 ˂ 0.05, meaning that there is a significant difference in the improvement of problem solving skills between the experimental class and the control class. So it can be concluded that the application of the RANDAI learning model has a positive effect in improving problem solving skills on fungi material in class X SMA Pertiwi 1 Padang.